A proposal to implement circular economy practices in the milk production chain in the municipality of Wenceslau Braz - Ribeiro Fortes, Ana Paula; de Nadae , Jeniffer; García Sánchez, Jesús Antonio (Revista Brasileira de Engenharia de Biossistemas, 2024)
The dairy industry has experienced significant changes since 2021, characterized by increased milk production and a concurrent exodus of producers as the sector becomes more professionalized and modernized. A pressing concern within this chain is the management of whey, a byproduct of cheesemaking. While whey is nutritionally rich, its improper disposal poses a significant environmental threat. A shift towards a Circular Economy (CE) is imperative to foster sustainable growth in the dairy sector. The CE can create new markets, generate income, and mitigate environmental impacts by revaluing whey as a potential raw material. This paper proposes implementing circular practices in the milk production chain. Using the case study methodology, it evaluates their implications for sustainable rural development in a small town in Minas Gerais. The case study was conducted in a dairy located in the municipality of Wenceslau Braz, in the state of Minas Gerais, Brazil. The rural dairy industry in Wenceslau Braz significantly impacts the local economy, providing jobs, promoting local products, and sustaining rural life. However, implementing circular economy practices faces challenges due to inadequate technology for recycling whey in small-scale operations. To address this problem, it is necessary to support micro and small businesses through financial services and research investments. The dairy industry discussed in this paper is already engaged in circular practices, such as donating whey for animal feed and producing cheese bread.